2015
DOI: 10.1007/s11356-015-4469-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sunlight and oxidative treatment on measured PAH concentrations in biochar

Abstract: The concentration changes of 18 different polycyclic aromatic hydrocarbons (PAHs) in two different biochars were assessed after (1) chemical oxidative treatment with a solution of H2O2 and Na2S2O8, (2) exposure to sunlight with intermittent wetting, and (3) exposure to sunlight with intermittent wetting after mixing in ZnO and Na2S2O8. Chemical oxidative treatment of biochars derived from gasified wood biochar and a gasified wood/Arundo donax mixture led to decreases in six-ring PAHs, but overall significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Marchal et al showed that the sorption of PAHs to biochar limits its degradation in biochar-amended soils but not in pure biochar (Marchal et al, 2013a(Marchal et al, , 2013b. In Khalid and Klarup (2015), the PAH concentration in biochar was strongly reduced by exposure to sun light and water addition which is encouraging as it suggests that PAH concentrations in biochar can be reduced rapidly in the environment after soil application despite being strongly sorbed.…”
Section: Potential Toxic Effects and Fate Of Pahs In Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Marchal et al showed that the sorption of PAHs to biochar limits its degradation in biochar-amended soils but not in pure biochar (Marchal et al, 2013a(Marchal et al, , 2013b. In Khalid and Klarup (2015), the PAH concentration in biochar was strongly reduced by exposure to sun light and water addition which is encouraging as it suggests that PAH concentrations in biochar can be reduced rapidly in the environment after soil application despite being strongly sorbed.…”
Section: Potential Toxic Effects and Fate Of Pahs In Biocharmentioning
confidence: 99%
“…The different status of NAP compared with the rest of the 16 US EPA PAHs has been recognised and after recommendation by the European Scientific Committee on Food in 2005, the EU Commission established a list of 15 priority pollutants for investigation in food which did not include NAP (nor some other lower toxicity PAHs such as phenanthrene) (EU Commission Recommendation, 2005). The PAHrelated risk associated with biochars containing similar total PAH concentration can vary greatly, depending on PAH composition; NAP plays an important role as it typically comprises ≥40% of the total PAH concentrations in biochar (Bucheli et al, 2015;Freddo et al, 2012;Hilber et al, 2012;Khalid and Klarup, 2015;Kloss et al, 2012;Quilliam et al, 2013;Yargicoglu et al, 2015). It is clear that even biochar with a high content of total 16 US EPA PAHs may not pose environmental or health risk if NAP is the major PAH component.…”
Section: Introductionmentioning
confidence: 99%
“…The sorption capacity of biochar decreased markedly in soil within 2 years due to aging, and it was estimated to equal unamended soil within 2.5 years ( Ren et al., 2018 ). Exposure of biochar to sunlight and rain can reduce the cumulative PAHs concentration through volatilisation and desorption of mainly the low molecular weight PAHs ( Khalid and Klarup, 2015 ). Therefore, environmental weathering can lower contaminants level in biochar.…”
Section: Challenges and Limitations Of Biochar Applicationmentioning
confidence: 99%
“…There has been some change since then, but even where the char has been produced in-house, and/or the gasifier/pyrolyser is described, detail sufficient to draw conclusions on PAH formation (e.g. actual core temperature and reactor stability during experiments) is invariably omitted [ 6 , 18 , 26 32 ]. This applies across all scales from low- to high-tech industrial systems [ 18 ], and the situation goes some way to explaining why PAH concentrations in biochar have been observed to range from 0 ≤ µg g −1 ≤ 3000.…”
Section: Introductionmentioning
confidence: 99%
“…No other information provided 117 ≤ µg g −1 ≤ 172. Additionally, 48 ≤ µg g −1 ≤ 53 reported for combined quantity of naphthalene 1- and 2-methyl [ 32 ] two different gasifier system used and mode of operation described in detail. However, only a range of design operating temperatures given rather than results of temperature during actual production 0.69 ≤ µg g −1 ≤ 5.…”
Section: Introductionmentioning
confidence: 99%